Two Layer Security Combining MSB Based Steganography and RSTEG With Cryptography - P I, Sumayya; K, Sheena Kurian (IJRDO -Journal of Computer Science Engineering, 2015)
The sharing of sensitive information along a common communication channel has become inexorable in thisinternet era. Variant techniques are available to ensure the security of private data according to the specific needs. Anew way of securing the data is proposed here which makes use of the combination of two data securing techniques.AES cryptography is utilized in combination with a new steganographic technique. The technique improves the security,as the message is not directly embedded in the cover image, instead a status check is done. Accordingly an indication isprovided whether at a calculated bit position of the pixel, the actual message bit or its toggled form is present. Theposition to be compared with message bit is based on the users choice, which specifies which all color components of thepixel to be used. The proposed method uses the MSB bits of pixels for decision making. Multilevel steganography is doneby incorporating retransmission steganography. It is effortful for a snooper to retrieve the actual message as it is verydifferent from the common LSB method. The Mean Square Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) andthe histogram differences can be used to measure the image quality and efficiency of the technique